Evaluasi Pengelolaan Obat di Instalasi Farmasi Rumah Sakit Umum Daerah Kabupaten Muna Tahun 2014 - Ihsan, Sunandar; Amir, Sry Agshary; Sahid, Mohammad (Fakultas Farmasi Universitas Halu Oleo, 2015)
This study aims to evaluate the processÂ drugs management based on indicators i.e. planning, procurement, storage and distribution of drugs in Pharmacy Installation of Munaâ€™s General Hospital in 2014. Data were collected retrospectively by taking reports-inventory forms, prescription sheet patients, drug plan data, drug stocks cards, prescription patient sheets, output data of the drug as well as concurent form of services and time recipes data with random sampling method.Â The results were obtained the percentage of availability amount 100% and the percentage of planning 9,15% in the frequency of drug procurement as much as 1, 2, 3, and 4 times with the number of drug items 72, 20, 4, and 1 item of drugs. Match reports card stock inventory taking medication 91,30%, and the percentage of expired or defective drugs by 0.33%, the percentage of dead stock 7,96%, and the percentage of the drug emptiness time 2,19%, percentage of served drugs 97.95%, the average service time of non-concoction recipe 3,16 minutes, and the average service time compounded prescription 6.10 minutes. Improvement on drug management is required in order to obtained standard values in all categories. Keywords: Evaluation, Drug Management, Pharmacy Installation, and Hospital.